Test validation process of tactical knowledge in tennis: The influence of practice time and competitive experience - Aburachid, L. M. C.; Morales, J. C. P.; Greco, P. J. (International Journal of Sports Science, 2013)
This paper describes the development process to test validation of t declarative tactical knowledge in tennis since the scenes definition to the items validation up to the application of pilot test. Based on the theory of the latent trait the psychometric requirements searching for the validation of the constructs perception and decision making, were properly respected. Was reached to satisfactory values of content validity (0.89), reliability with a=0,6518 and difficulty items index. After the test application there was a significant correlation between the perception and decision making (r=0,612). Were found evidences of practice time and participation in competitions in higher levels influences in improvement of the tactical knowledge level of young tennis players.